THE ENGLISH LITERACY DEVELOPMENT AT ISLAMIC HIGH SCHOOLS: AN EVALUATION - Suadi, Suadi (Journal of English Education and Linguistics, 2023)
English literacy is a captivating topic among language scholars, educators, and learners. English literacy culture in Indonesian schools still has been in dismaying condition. This study aimed to unveil hindrances and relevant solutions to realize the English literacy atmosphere at three state Islamic senior high schools (Madrasah Aliyah Negeri) in Sumatera Utara. Observation, in-depth interviews, and documentation were swiftly executed during the data collection process. Participants, consisting of five English teachers from three different State Islamic senior high schools, were willingly recruited to be interviewees. The data afterward were analyzed based on thematic analysis. Results highlighted two factors decelerating the English literacy environment at schools. Moreover, six crucial ways were unmasked for accelerating English literacy at school into positive progress.